(untitled) (Polifonia, 2015)
Neste artigo analisa-se o filme “WALACHAI”, obra que contextualiza uma comunidade de imigrantes alemães do sul do Brasil. Abordam-se aspectos teóricos da sociolinguística e dos estudos culturais para compreender o fenômeno da concepção identitária do povo à luz de fatores como hibridismo cultural e heterogeneidade linguística. Estuda-se a história da imigração alemã como efeito da globalização e como elemento que contribuiu para a constituição do povo brasileiro. Verifica-se que a comunidade vive em um contexto de entre-línguas, realidade por vezes desprestigiada pela própria população. PALAVRAS-CHAVE: identidade, hibridismo cultural, heterogeneidade linguística IDENTITY, CULTURE AND LANGUAGE IN THE CONTEXT OF GERMAN IMMIGRATION: AN ANALYSIS OF THE FILM "WALACHAI" ABSTRACT: This paper analyzes the movie “WALACHAI”, which contextualizes a community of German immigrants in Southern Brazil. It focuses on the theoretical aspects of sociolinguistics and cultural studies to understand the population’s identity conception through elements such as cultural hybridity and linguistic heterogeneity. It also studies the history of German immigration as a result of globalization and as an element that constitutes Brazilian people. It is possible to verify that the community lives in a “between languages” context, a reality sometimes discredited by the population. KEYWORDS: identity, cultural hybridism, linguistic heterogeneity